Administrative Activity of the Security Service of Ukraine as the Basis for Ensuring Critical Infrastructure (Law and Safety, 2020)
The subject matter of the study is administrative activities of the Security Service of Ukraine. The purpose of the research is to reveal the specific features of administrative activities of the Security Service of Ukraine as the basis for ensuring the critical infrastructure of Ukraine.This study is focused on the current tendencies in interpreting the nature of administrative activities, studying the origin and application of the concept of “critical infrastructure” and revealing the features of administrative activities of the Security Service of Ukraine aimed at protecting critical infrastructure of Ukraine.The obtained information allowed us to clarify the concepts of “administrative activity” and “administrative and public activity” of the Security Service of Ukraine and to prove the exceptional importance of this activity to ensure the protection of critical infrastructure of our state. The clarification of administrative and legal conceptual apparatus, implemented in this research, creates the basis for further research and amendments to national regulatory acts.The data obtained during the research allow us to conclude that approaches to determining the content of such a category as “threats to national security” are changed with the development of the concept of “critical infrastructure”. This should be reflected in administrative activities of the Security Service of Ukraine, and should be enshrined in the relevant regulatory acts and create a solid foundation for the protection and security of critical infrastructure of Ukraine.
Keywords: administrative activity; administrative and public activity; critical infrastructure; national security; Security Service of Ukraine; threats to national security